State Building, State Dismantiling, and the Military in Ecuador - North, Liisa (2006)
This article deals with some military governments efforts to build a state that could serve broad public rather than simply narrow private interests, and it does so with reference to the obstacles rooted in Ecuador’s patterns of social-political domination that have undercut those efforts. The article begins with a description of contrasts between the so-called “revolutions” of July 1925 and January 2000. It then briefly reviews key moments in state building from 1925to 1979, the policies of state dismantling pursued by civilian elites since the transition to democracy in the latter year, and military responses to recent social protest.